The Right to Housing. (May 2019) - Wells, Katy
The issue of justice in housing is rarely discussed in political philosophy. Yet, housing crises such as that currently faceSd by the UK highlight the importance of work in this area. In this article, I address the issue of housing justice by defending a basic right to housing. The right is in the first instance specific to a particular context, that of a Western liberal society. I defend a positive right to exercise a set of property rights called 'lease rights' over a self-contained living space of a certain standard, for a minimum term of 3 years. An important feature of this right is that it is a right to live alone. Where individuals have to live in communal housing because they lack the resources to do otherwise, their basic rights are violated. The account provides a distinctive understanding of how a government's housing policy can fail its citizens.